High frequency tan delta measurement method for 132kV transmission underground cables - Avinash A.R.; Chakrabarty C.K.; Permal N. (Maxwell Science Publications, 2023)
Tangent Delta is a measurement technique to investigate cables insulation strength. Current techniques utilize Very Low Frequency (VLF) at 0.1 Hz and power frequency at 50 Hz. However, high voltages are required, thus requiring larger space and cost. Proposed method of tangent delta testing utilizes High frequency Low voltage diagnoses. The phase between the current and the voltage is utilized to determine the tangent delta (tan ?). The aim of this study is to develop a low voltage high frequency tangent delta measurement method and test if it can discriminate manufactured 132 kV good conditioned cable sample from defect induced cables with void, scotched and contamination in its insulation. Impurities are clearly discriminated using this method. Comparison of Tangent Delta of cables manufactured simultaneously in good condition and defect induced is performed using High Frequency Tangent Delta method and in 50 Hz conventional method to validate the effectiveness of the measurement technique. The High Frequency AC setup utilizes a small testing environment which can sample small lengths with minimum 1 m length of cable. The small lengths will result in the reduction of total capacitance of the cable but using High Frequency induces high electric stress on XLPE layer thus resulting in measureable dielectric current. Maxwell Scientific Organization, 2015.